2019
DOI: 10.2147/prbm.s221670
|View full text |Cite
|
Sign up to set email alerts
|

<p>The relationship between the feedback environment and creativity: a self-motives perspective</p>

Abstract: BackgroundFor companies, employee creativity is vital to gaining competitive business advantages. Research regarding creativity has focused on contextual factors such as feedback, but results of studies on the relationship between feedback and creativity are inconsistent; further, only a handful of studies have been carried out from the perspective of coworkers. In this study, we aimed to analyze the association between the coworker feedback environment and creativity, to test the mediating role of feedback mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…This is associated with Rabeeh's (2004) finding that collaboration among teachers establishes trust and develops communication in the teaching profession. This finding is also consistent with the study of and Gong, Shan, and Yu (2019) where individual creativity has a significant and positive relationship with the feedback environment. Moreover, the result of this research is consistent with Yu's (2016) study that as the human resources in the organization, teachers can use the received feedback findings from students to improve their instructional strategies.…”
Section: Influence Of Feedback Environment Practices On School Climatesupporting
confidence: 92%
“…This is associated with Rabeeh's (2004) finding that collaboration among teachers establishes trust and develops communication in the teaching profession. This finding is also consistent with the study of and Gong, Shan, and Yu (2019) where individual creativity has a significant and positive relationship with the feedback environment. Moreover, the result of this research is consistent with Yu's (2016) study that as the human resources in the organization, teachers can use the received feedback findings from students to improve their instructional strategies.…”
Section: Influence Of Feedback Environment Practices On School Climatesupporting
confidence: 92%
“…Among the available literatures, based on the theoretical framework of creativity investment, studies on the relationship between creativity and environment (e.g., Cole et al, 1999 ; Dul and Ceylan, 2011 ; Gong et al, 2019 ), sense (e.g., Chessick, 1996 ; Berg and Hallberg, 1999 ; Fraser et al, 2021 ), and the interaction between creativity and emotion (e.g., Kopcso and Lang, 2017 ; Mastria et al, 2019 ; Xu et al, 2021 ) have also received much attention. One mainstream consensus among many studies is that a favorable environment promotes creativity (e.g., Cole et al, 1999 ; Dul and Ceylan, 2011 ; Gong et al, 2019 ). Another mainstream view is that positive emotions and perceptions promote creativity (e.g., Rouff, 1975 ; Humke and Schaefer, 1996 ; Yawen et al, 2021 ).…”
Section: Theoretical Basis and Hypothesismentioning
confidence: 99%
“…Despite differences in perspective, all conceptualizations share the commonality that the sense of place is a mix of environment and perception ( Zhu and Liu, 2011 ; Juan, 2014 ; Tingting and Zhao, 2015 ). Currently, few studies have investigated into the relationship between sense of place and creativity; however, some researchers have focused on the relationship between environment and creativity (e.g., Dul and Ceylan, 2011 ; Gong et al, 2019 ; Pugsley and Acar, 2020 ), even arriving at the conclusion that environment is positively correlated with creativity ( Richards, 1992 ; Dul and Ceylan, 2011 ; Pugsley and Acar, 2020 ); i.e., the more positive the environment, the higher the level of creativity. In addition, some studies have reported on the relationship between perception (or emotion) and creativity (e.g., Chessick, 1996 ; Humke and Schaefer, 1996 ; Rui et al, 2021 ).…”
Section: Theoretical Basis and Hypothesismentioning
confidence: 99%
“…In consideration of the possible influence of common method bias—which had been observed in many previous research studies (Chun et al, 2012; Gong et al, 2019)—we distributed two separate sets of questionnaires each amongst the protégés and the mentors, allowing an interval of 3 months to procedurally control the common method bias. At the first time point, the mentors responded to a questionnaire that extracted data pertaining to their demographic variables and details regarding their mentorship, whereas the protégés answered a questionnaire centred around mindfulness.…”
Section: Methodsmentioning
confidence: 99%